The Influence of Project Based Learning and Critical Thinking Learning Models on Science Learning Outcomes of Grade V Elementary School - Sudarti Sudarti; Happy Karlina Marjo; Amalia Sapriati (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Background This study investigates the effect of the Project-Based Learning (PjBL) model and students’ critical thinking skills on science learning outcomes of fifth-grade elementary school students. The research employed an experimental method with a 2×2 factorial design, involving two independent variable learning models (PjBL) and conventional learning) and critical thinking skills (high and low) and one dependent variable, namely science learning outcomes. The participants consisted of 67 fifth-grade students from SDN Pejaten Barat 06, South Jakarta, divided into an experimental group (34 students) and a control group (33 students). Data were collected using science learning outcome tests, critical thinking questionnaires, observation sheets, interviews, and documentation. Instrument validity and reliability were tested prior to data analysis. The data were analyzed using two-way ANOVA and t-tests with the assistance of SPSS. The results showed that the application of the Project-Based Learning model had a significant positive effect on students’ science learning outcomes. The experimental group achieved a higher average posttest score (92.13) compared to the control group (77.39). Students’ critical thinking skills also significantly influenced learning outcomes, with students who demonstrated high critical thinking skills achieving better results than those with lower levels. Furthermore, the analysis revealed a significant interaction between the PjBL model and critical thinking skills on science learning outcomes, indicating that PjBL is more effective when accompanied by the development of students’ critical thinking abilities. In conclusion, the Project-Based Learning model integrated with critical thinking development is effective in improving science learning outcomes, promoting active participation, collaboration, and higher-order thinking skills. This learning model is recommended as an innovative instructional approach to enhance the quality of science learning in elementary schools in accordance with 21st-century educational demands.